LINC00957 Acted as Prognostic Marker Was Associated With Fluorouracil Resistance in Human Colorectal Cancer - Zhang, Li Hua; Li, Long Hai; Zhang, Peng Fei; Cai, Yan Fei; Hua, Dong (Frontiers in Oncology, 2019)
Colorectal cancer (CRC) is one of the most prevalent digestive tumors in China. Recent studies indicate that long intergenic non-coding RNAs (lincRNAs) play a crucial role in predicting survival for CRC patients. However, the novel lincRNA, LINC00957, is largely unclear in CRC. The purpose of the current study was to determine LINC00957 expression, assess its the clinical significance and explore the potential mechanism in CRC. The qRT-PCR was used to quantify the expression levels of LINC00957 in tissues and cell lines. Our research revealed that LINC00957 was significantly higher expression in CRC. In addition, the LINC00957 expression was associated with TNM stage and chemotherapy outcome, but age, gender, tumor size, histological grade, primary tumor location. CRC patients with high LINC00957 expression level showed poor overall survival (P = 0.002). Multivariate survival analysis indicated that LINC00957 was a prognostic factor for CRC patients (P = 0.010). Mechanically, inhibition of LINC00957 expression reversed 5-FU resistance by down-regulating P-gP. In summary, our study indicated that this novel lncRNA expression signature might be a useful biomarker of the prognosis and therapeutic target for CRC patients.